1981
DOI: 10.1002/cber.19811140523
|View full text |Cite
|
Sign up to set email alerts
|

Neue Gold‐Carben‐Komplexe durch Carbenübertragung

Abstract: Aus Wolfram‐Aryl‐ und ‐Alkylcarben‐Komplexen lassen sich mit Tetrachlorgoldsäure die entsprechenden Gold(I)‐Carben‐Komplexe (2a–e, 4) in guten Ausbeuten synthetisieren. Die Carbenübertragung auf das Gold erfolgt unter Konfigurationserhaltung am Carbenliganden. Der Mechanismus der Reaktion sowie spektroskopische Daten der Komplexe werden diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 10 publications
0
31
0
3
Order By: Relevance
“…[16][17][18] Indeed, reaction of 7 with [(Cy 3 P)Au]NTf 2 furnished 8 in good yield (Scheme 2). [16][17][18] Indeed, reaction of 7 with [(Cy 3 P)Au]NTf 2 furnished 8 in good yield (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Indeed, reaction of 7 with [(Cy 3 P)Au]NTf 2 furnished 8 in good yield (Scheme 2). [16][17][18] Indeed, reaction of 7 with [(Cy 3 P)Au]NTf 2 furnished 8 in good yield (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
“…Zuschriften work exceedingly well for the preparation of stabilized Fischer-type carbene complexes of gold. [16][17][18] Indeed, reaction of 7 with [(Cy 3 P)Au]NTf 2 furnished 8 in good yield (Scheme 2). Although the preparative experiments were carried out at ambient temperature, NMR spectroscopy revealed that this formal transmetalation proceeds even at À50 8C.…”
Section: Methodsmentioning
confidence: 99%
“…[55][56][57] Wegen ihrer wahrscheinlichen Rolle als reaktive Zwischenstufen in vielen platin-und goldkatalysierten Reaktionen ist es angezeigt, die heute verfügbaren strukturellen Informationen über Carbenkomplexe dieser späten Über-gangsmetalle näher zu erörtern. Dabei sei zunächst festgehalten, dass typische Fischer-Carbenkomplexe des Chroms, Molybdäns und Wolframs mit entsprechenden Goldsalzen einen raschen Carben-Transfer eingehen, [58] was auf eine hohe thermodynamische Stabilität von Goldcarbenen hinweist, die sowohl für Au III als auch für Au I bekannt sind; letztere sind erwartungsgemäß linear koordiniert (Abbildung 9). [59] Allerdings ist aus den molekularen Festkörperstrukturen klar ersichtlich, dass die C-Au-"Carben"-Bindung solcher Spezies allenfalls geringfügigen Doppelbindungscharakter aufweist.…”
Section: Grundlagen Der Carbophilen Aktivierungunclassified
“…[5±7] However, the transfer of alkoxycarbene ligands has been reported only for [Mo{CPh(OMe)}-(CO)(Cp)(NO)] to [Fe(CO) 5 ] [8] and [W{CPh(OMe)}(CO) 5 ] to H[AuCl 4 ]. [9] Very recently Sierra et al have proposed palladium biscarbene complexes as the active intermediates in the palladium-catalyzed dimerization of alkoxycarbene ± chromium complexes. [10,11] In the context of our studies on copper-catalyzed coupling reactions of Fischer carbene complexes we report here on 1) the cross-coupling of Fischer chromium ± carbene complexes with ethyl diazoacetate (EDA), and 2) the isolation and full characterization of the first alkoxycarbene complex of copper(i).…”
mentioning
confidence: 99%